A Biomimetic Approach toward Enhancing Angiogenesis: Recombinantly Expressed Domain V of Human Perlecan Is a Bioactive Molecule That Promotes Angiogenesis and Vascularization of Implanted Biomaterials. Issue 17 (14th June 2020) - Lin, Xiaoting; Tang, Fengying; Jiang, Shouyuan; Khamis, Heba; Bongers, Andre; Whitelock, John M.; Lord, Megan S.; Rnjak‐Kovacina, Jelena
Abstract: Angiogenic therapy involving delivery of pro‐angiogenic growth factors to stimulate new blood vessel formation in ischemic disease is promising but has seen limited clinical success due to issues associated with the need to deliver supra‐physiological growth factor concentrations. Bio‐inspired growth factor delivery utilizing the native growth factor signaling roles of the extracellular matrix proteoglycans has the potential to overcome many of the drawbacks of angiogenic therapy. In this study, the potential of the recombinantly expressed domain V (rDV) of human perlecan is investigated as a means of promoting growth factor signaling toward enhanced angiogenesis and vascularization of implanted biomaterials. rDV is found to promote angiogenesis in established in vitro and in vivo angiogenesis assays by potentiating endogenous growth factor signaling via its glycosaminoglycan chains. Further, rDV is found to potentiate fibroblast growth factor 2 (FGF2) signaling at low concentrations that in the absence of rDV are not biologically active. Finally, rDV immobilized on 3D porous silk fibroin biomaterials promotes enhanced vascular ingrowth and integration of the implanted scaffolds with the surrounding tissue. Together, these studies demonstrate the important role of this biologically active perlecan fragment and its potential in the treatment of ischemia in both native and bioengineered tissues. Abstract : A biomimetic growth factor delivery approach utilizing the native signaling roles of extracellular matrix is described. C‐terminal region of perlecan (rDV) is shown to promote angiogenesis by signaling endogenous and exogenous growth factors at low concentrations in its soluble form and when immobilized on a biomaterial, making it a promising approach toward angiogenic therapy for the treatment of ischemic disease.